Evaluation of the long‐term effect of biochar on properties of temperate agricultural soil at pre‐industrial charcoal kiln sites in Wallonia, Belgium. (7th December 2016) - Hardy, B.; Cornelis, J.‐T.; Houben, D.; Leifeld, J.; Lambert, R.; Dufey, J. E.
Abstract : Research on biochar has increased, but its long‐term effect on the fertility of temperate agricultural soil remains unclear. In Wallonia, Belgium, pre‐industrial charcoal production affected former forested areas that were cleared for cultivation in the nineteenth century. The sites of traditional charcoal kilns, largely enriched in charcoal residues, are similar to soil amended with hardwood biochar more than 150 years ago. We sampled 17 charcoal kiln sites to characterize their effect on soil properties compared with adjacent reference soils. Charcoal‐C content was estimated by differential scanning calorimetry. The kiln soil contains from 1.8 to 33.1 g kg −1 of charcoal‐C, which markedly increases organic C:N and C:P ratios. It also contains slightly more uncharred soil organic carbon (SOC) than the reference soil, which accords with larger total N content. We measured a small increase in nitrates in the kiln soil that might relate to greater mineralization and nitrification of organic N. Frequent application of lime raised the pH to values close to neutral, which offset the residual effect of charcoal production on soil acidity. A cation exchange capacity (CEC) of 414 cmolc kg −1 was estimated for charcoal‐C, whereas that of uncharred SOC was 213 cmolc kg −1 . Despite the large CEC of the kiln soil, exchangeable K + content was no different from the adjacent soil, whereas exchangeable Ca 2+ and Mg 2+ contents were considerably larger. Charcoal enrichment has little effect on available, inorganic and total P, but it can form strong complexes with Cu, which reduces the availability of the metal. Biochar is very persistent in soil; therefore, long‐term implications should not be overlooked. Highlights : Charcoal kiln soil contains from 1.8 to 33.1 g kg −1 of charcoal‐C, which raises C:N and C:P ratios. Charcoal‐C content was estimated by differential scanning calorimetry. We estimated a CEC of 414 cmolc kg −1 for charcoal‐C and 213 cmolc kg −1 for uncharred SOC. Retention of exchangeable K + remained unaffected by charcoal but that of Ca 2+ and Mg 2+ increased.